2021
DOI: 10.48550/arxiv.2112.12954
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitivity studies on the CKM angle $γ$ in $Λ_b^0 \to DΛ$ decays

Abstract: The sensitivity of the CKM angle γ in Λ 0 b → DΛ decays has been studied using the decay parameter α as an observable in addition to the decay rate asymmetry. Feasibility studies show that adding this observable improves the sensitivity on γ by up to 60% and makes the decays one of the most promising places to measure angle γ and to search for CP violation in b-baryon decays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…CP violation (CPV), which is an important component of the Standard Model (SM) of particle physics [1], has been observed in K , B, B s and D meson decay processes. Theoretical investigations of CPV have been performed in baryon decay processes [2][3][4][5][6][7][8][9][10][11][12][13][14]. It has been shown that there can be relatively large CP asymmetries (CPAs) in some decays of bottom baryons [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CP violation (CPV), which is an important component of the Standard Model (SM) of particle physics [1], has been observed in K , B, B s and D meson decay processes. Theoretical investigations of CPV have been performed in baryon decay processes [2][3][4][5][6][7][8][9][10][11][12][13][14]. It has been shown that there can be relatively large CP asymmetries (CPAs) in some decays of bottom baryons [6].…”
Section: Introductionmentioning
confidence: 99%
“…One such observable is the decay parameter in two-body weak decay processes of baryons. Typical examples include 0 → pπ − and 0 b → D 0 , where the decay parameter and the associated CPAs of the former channel have been measured by BESIII through baryon-anti-baryon pair production J/ψ → 0 0 [25], and those of the latter were proposed for extracting the Cabibbo-Kobayashi-Maskawa (CKM) phase γ through the dual weak cascade decays 0 b → D 0 with 0 → pπ − [2,12,13]. In both cases, the decay parameters can be related to forwardbackward asymmetries (FBA) of the final particle distributions in certain reference frames.…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of γ via Λ b → ΛD with D = D 0 , D 0 , D 1,2 has been given in Refs. [19,20]. However, a systematic study of the sequential decays with the helicity formalism is still missing.…”
Section: Introductionmentioning
confidence: 99%